Knowledge and attitude of medical interns about doping and its regulations - Hassabi , Mohammad; Salehi , Shahin; Poursaeidesfahani , Mehrshad; Abedi Yekta, Amir Hosein; Parsoon, Ali; Mahdaviani, Behnaz (Researcher Bulletin of Medical Sciences, 2020)
Objective: Doping is known as an important public health problem. Prominent sports events can be blemished due to doping. The role of general practitioners as an important part of the health system in the prevention of doping is obvious. Previous studies have shown they have been presumed themselves ill-prepared in dealing with this topic. This study set out to investigate the amount of knowledge and attitude among medical interns toward doping. Materials and Methods: This cross-sectional study was conducted on 100 medical interns in Taleghani hospital, Tehran, Iran Subjects were asked to complete a 35-item questionnaire. The questionnaire consisted of four parts: demographic data, status of physical activity, knowledge, and attitude. Knowledge was measured by questions regarding identifying prohibited drugs, adverse effects of banned drugs, WADA as an original source of published list of prohibited drugs, and regulations related to anti-doping rules violation. The attitude was measured based on a 5-point Likert scale. The more negative attitude toward doping was shown by higher scores. Results: The mean age was 25.39+/-1.43. Only 8% of students were familiar with WADA as an original source of doping. Approximately 90% of students were not aware of sanctions of anti-doping rules infraction. 65%, 33% and 2% of our subjects had poor, good and very good knowledge respectively. The mean score of attitude was 19.68+/-2.88. Conclusion: Our findings revealed, the senior medical students had negative attitudes toward doping and also their level of knowledge was poor in this regard.